Dynamic Modeling of Water Consumption Management in the Khuzestan Plain - Zeidvand, Ghorban; Hashemzadeh khorasgani, Gholam Reza; Alirezaei, Aboutorab (Management Strategies and Engineering Sciences, 2025)
The purpose of the present article is to develop a dynamic model for water consumption management in the Khuzestan Plain. Data collection was conducted through both library-based and field-based methods, employing a field analysis approach. Data analysis was performed using Vensim software. One of the prominent approaches in water resource allocation is the use of system dynamics methodology. Predicting behavioral changes in water resource systems under the influence of scenario-based and integrated policy interventions can support the optimal utilization of these resources. The system dynamics approach to water resource management in the agricultural sector of the Khuzestan Plain suggests short-, medium-, and long-term water consumption management strategies after examining current conditions. Under drought conditions, a shift in cropping patterns should be prioritized by planning authorities in responsible organizations. Accordingly, in recent years, a substantial portion of the land previously allocated to sugar beet and rapeseed—crops known for high water consumption—should be reduced. In collaboration with agricultural cooperatives, farmers should be encouraged to increase wheat cultivation. Changing cropping patterns across various cities can improve water demand in the agricultural sector. Given the rainfall levels in the province, farmers can replace high-water-demand crops with wheat to optimize water savings. Altering the cropping pattern not only increases wheat production in the province but also curbs excessive water use in this sector. In the industrial sector, the system dynamics approach to water resource management in the Khuzestan Plain identifies the direct use of potable water by industries as a major challenge for responsible organizations. Many of these industries have been established at high costs, yet initial planning for their water supply was inadequate. As a result, citizens frequently face shortages of drinking water. In the domestic sector, applying the system dynamics approach to water resource management in the Khuzestan Plain suggests that appropriate management and planning—along with promoting a water-saving culture—can largely alleviate citizens’ deprivation from potable water. For instance, public education and awareness campaigns regarding efficient water use, planting drought-resistant and climate-compatible vegetation, detecting and repairing leaks in faucets and plumbing fixtures, utilizing unused water sources, employing water-retaining irrigation gels, reducing shower time, avoiding car washing with water hoses, and preventing the hosing down of streets and sidewalks can significantly minimize household water consumption.